Evaluasi Kesesuaian Lahan Untuk Komoditi Padi, Jagung dan Bawang Merah pada Lahan Bukaan Baru di Kampung Bokem Distrik Merauke - Mangera, Yosefina; Wahida, Wahida; Yesnat, Christofol (AGRICOLA, 2022)
The availability of complete land resource data and information is needed to support sustainable agricultural development programs. The purpose of this study was to determine the level of land suitability as well as the limiting factors for rice, corn and shallots in the newly opened land of Bokem Village, Merauke District. Soil samples taken from the field were analyzed in the laboratory. Parameters observed were soil texture, C-organic, N-total, P2O5, K2O, CEC, and DHL. Data analysis was carried out by matching or comparing land requirements for plants and land properties in the study area. The results of this comparison show the level of land suitability for corn, soybeans and peanuts which include S1 (very suitable), S2 (appropriate), S3 (marginally suitable), N1 (currently not suitable) and N2 (permanently inappropriate). The results showed that the land suitability class for lowland rice was classified as marginal suitability class (S3) with limiting factors for nutrient retention (f) and available nutrients (n). For corn plants belonging to the current suitability class are not suitable (N1) with limiting factors for nutrient retention (f) and available nutrients (n), while for shallot plants (S3) with limiting factors for water availability (w) nutrient retention (f) and available nutrients (n). Basically the existing limiting factors can be corrected by fertilizing and liming.